Islamic Corporate Governance and The Performance of Sharia Banks - Setiyobudi, Ichsan; Windyastuti, Windyastuti (RSF Conference Series: Business, Management and Social Sciences, 2021)
This study analyzes the influence of Islamic Corporate Governance (ICG) on the performance of sharia banks. This study uses a panel data regression analysis tool. The research sample includes 12 Islamic banks from 2009 to 2019. Based on the 2020 Islamic banking statistics, the number of sharia banks is 12. The sampling technique used is the convenience sampling method. The results showed that Islamic corporate governance has a positive effect on the performance of sharia banks. ICG has a positive effect on financial performance and managerial behavior. Reporting quality and profits are better after implementing strict ICG. Similarly, the size of the bank as a control variable has a positive effect on the performance of Islamic banks.